Kubus Augmented Reality (AR) 3D Sebagai Media Pembelajaran Inovatif untuk Meningkatkan Maharah Kalam Mahasiswa Generasi Z / 3D Augmented Reality (AR) Cubes as Innovative Learning Media to Improve the Speaking Skills of Generation Z Students - Devi Eka Diantika; Ahmad Amirul Kholid (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2026)
Generation Z, as digital natives, requires interactive, visual, and engaging learning media—particularly for developing Arabic speaking skills, which students often find challenging. This study aims to develop and evaluate the effectiveness of a 3D Augmented Reality (AR) Cube as an innovative learning medium to enhance Arabic speaking proficiency among university students. Using the ADDIE-based Research and Development (R&D) model, the study was conducted with 38 students from the Arabic Language and Literature Study Program at UNUGIRI over four weeks (eight sessions). Data were collected through expert validation, student response questionnaires, classroom observation, and pre-test/post-test assessments. Results show that the AR Cube was rated "highly valid" by both content (4.8/5.0) and media experts (4.6/5.0). Student feedback was overwhelmingly positive (86.3% agreement), and speaking skills improved significantly—from an average pre-test score of 63.4 to 86.5 post-test (+36.4%; p < 0.05, Cohen's d = 1.8). These findings confirm that a physical-digital hybrid AR medium effectively boosts both motivation and speaking competence, addressing key challenges in modern Arabic language instruction. However, the medium's effectiveness is partially dependent on access to compatible smartphones and stable internet connectivity. The AR Cube is thus recommended for integration into active, edutainment-based Arabic classrooms, with consideration of students' technological access.Generasi Z sebagai digital native membutuhkan media pembelajaran yang interaktif, visual, dan menyenangkan, terutama dalam pengembangan keterampilan berbicara bahasa Arab yang selama ini dianggap menantang. Penelitian ini bertujuan mengembangkan dan menguji efektivitas Kubus Augmented Reality (AR) 3D sebagai media pembelajaran inovatif untuk meningkatkan keterampilan berbicara mahasiswa. Menggunakan model Research and Development (R&D) ADDIE, penelitian dilaksanakan di Program Studi Bahasa dan Sastra Arab UNUGIRI terhadap 38 mahasiswa selama empat minggu (delapan pertemuan). Data dikumpulkan melalui validasi ahli, angket respons pengguna, observasi, serta pre-test dan post-test. Hasil menunjukkan bahwa Kubus AR dinyatakan sangat layak oleh ahli materi (skor 4,8) dan ahli media (skor 4,6). Respons mahasiswa sangat positif (86,3%), dengan peningkatan signifikan pada kemampuan berbicara: rata-rata skor naik dari 63,4 menjadi 86,5 (peningkatan +36,4%; p < 0,05; Cohen's d = 1,8). Temuan ini membuktikan bahwa integrasi media fisik-digital berbasis AR efektif meningkatkan motivasi dan keterampilan berbicara, sekaligus menjawab tantangan pembelajaran bahasa Arab di era digital. Efektivitas media ini sebagian bergantung pada ketersediaan smartphone yang kompatibel dan koneksi internet yang stabil. Media ini direkomendasikan untuk diadopsi dalam pembelajaran aktif berbasis edutainment dengan mempertimbangkan akses teknologi mahasiswa.